Cytotoxic, Anti-bacterial, and Wound-healing Activity of Prenylated Phenols from the Kurdish Traditional Medicinal Plant Onobrychis Carduchorum (Fabaceae) - Clericuzio, Marco; Hussain, Faiq H. S.; Amin, Hawraz Ibrahim M.; Bona, Elisa; Gamalero, Elisa; Giorgia, Novello; Lappano, Rosamaria; Talia, Marianna; Maggiolini, Marcello; Bazzicalupo, Miriam; Cornara, Laura (Planta Medica International Open, 2020)
Onobrychis carduchorum (Fabaceae) is a plant widely employed in Kurdish traditional medicine to cure wounds, inflammations, and other skin diseases. We could isolate ten different polyphenols from the acetone extract of this plant: 1–4 are isoflavones, having a genistein skeleton; 5–7 are flavanones, having a naringenin skeleton; and 8–10 are prenylated dihydro-stilbenes. In particular, 8–10 have been isolated, so far, only from Glycyrrhiza glabra (liquorice). Many of the above prenylated phenols showed significant toxicity on some human breast cancer cell lines, and a relevant growth inhibition of Staphylococcus aureus strains. In addition, 9 and 10 had marked wound healing activity. It is suggested that these bioactivities are responsible, at least partly, for the plant’s traditional use.
Keywords: Preparative Chromatography Extraction; Isolation; lc-MS Natural Products Analysis; Antimicrobial Molecular Targets and Activities; Fabaceae; Onobrychis carduchorum; Phenolics Natural Products Classes